Selling Crime by Subscription: W. M. Jackson and the Club de Novelas Laberinto/Clube de Novelas Labirinto. - Benedict, Nora (Hispanic Review)
Detective fiction became a popular, and profitable, literary genre in Latin America during the twentieth century. This rise to prominence can be attributed to many factors, but one of the most salient is the rapid development and expansion of the Latin American publishing industry. In this paper I examine how one publishing house, W. M. Jackson, capitalized on these trends through the development of a book-of-the-month club centered on detective fiction: the Club de Novelas Laberinto in Mexico and Argentina and its sister organization, the Clube de Novelas Labirinto in Brazil. In particular, I show how this club accentuates W. M. Jackson's keen eye for profitable business models in book publishing as well as this firm's talent for identifying marketable trends in literature.